ANALISIS KEMAMPUAN NUMERIK SISWA SMP DENGAN GAYA KOGNITIF FIELD DEPENDENT - Nurul Fadilah; Siti Khabibah; Nihayatus Sa’adah (Program Studi Pendidikan Matematika FIP UNHASY, 2022)
Numerical ability is ability of individuals to reason logically and mathematically in solving problem related to number. Numerical ability is problem in Al-Isma'iliyah Junior High School. Result of interview with the teacher, it is found that students counting ability are low and students learning behavior are diverse. Counting ability is one that can describe numerical ability. Indicators of numerical ability are; 1) ability to calculate mathematically, 2) think logically, 3) organize information to solve problem, 4) ability to identify patterns of numbers and their relationships and learning behavior can be influenced by cognitive style. This study aims to describe numerical ability of student with Field Dependent cognitive style. Type of research was descriptive qualitative research with the research subject was selected using purposive sampling based on the type of cognitive style. Data were collected by test and interview methods with the instrument are GEFT test, number test and interview guidelines. Student have high numerical ability if he was able to achieve minimum three indicators, medium two indicators, and low maximal one indicator. Results of the study showed that student with Field Dependent cognitive style had low numerical ability because he could’nt achieve all indicators.